Tissue Specific Esterase Expression In Indigenous Chicken Of Bangladesh - Shahjahan, RM; Muid, KA; Akter, QS; Tareq, KMA; Begum, RA; Begum, R; Khandoker, MAMY (Bangladesh Journal of Animal Science, 2012)
The present investigation was done in the esterase gene expression analysis of the Red Jungle fowl Gallus gallus of Bangladesh utilizing the polyacrylamide gel electrophoresis (PAGE) technique. Each allele produces a biochemical message that helps to produce various protein phenotypes those were expressed in the form of bands on the polyacrylamide gel bed. Altogether four different esterase bands were recorded in both Red Jungle (RJ) fowl and Naked Neck (NN) fowl of Bangladesh. These were denoted as Est-1 (2), Est-2(1), Est-3 (21) and Est-4 (13) based on the relative mobility on the gel. Among them Est-2 is very common in almost all tissues. Comparing the esterase in both genetic groups, their expression intensity even the relative mobility provided a unique feature that they were similar. The investigation indicates that esterase gene between the Red Jungle fowl and Naked Neck fowl of Bangladesh has a close relationship. DOI: http://dx.doi.org/10.3329/bjas.v38i1-2.9908 BJAS 2009; 38(1-2): 15-21